2005
DOI: 10.1248/bpb.28.2106
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperlipidemic Effect of Crocin Isolated from the Fructus of Gardenia jasminoides and Its Metabolite Crocetin

Abstract: Lipid metabolism normally maintains an elegant balance between synthesis and degradation. When the balance is lost, hyperlipidemia, such as hypertriglyceridemia and hypercholesterolemia, may develop. This can cause variety of serious diseases, such as arteriosclerosis, hypertension, obesity, diabetes, functional depression of some organs, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
112
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(121 citation statements)
references
References 18 publications
4
112
1
4
Order By: Relevance
“…The most potent inhibitor was crocetin, with an IC 50 value of 2.1 mg/mL. 109 In mice fed a high fat diet, crocetin and crocin inhibited the incremental increase in body weight compared with that of the control group. These compounds also significantly reduced epididymal fat pad mass.…”
Section: Crocin and Crocetinmentioning
confidence: 97%
“…The most potent inhibitor was crocetin, with an IC 50 value of 2.1 mg/mL. 109 In mice fed a high fat diet, crocetin and crocin inhibited the incremental increase in body weight compared with that of the control group. These compounds also significantly reduced epididymal fat pad mass.…”
Section: Crocin and Crocetinmentioning
confidence: 97%
“…Apoptosis and necrosis are important modes of neuronal death induced by cerebral ischemia, but in recent years a third method of death, autophagy, has been studied [1][2][3] . Autophagy, which involves the formation of autophagosomes and autophagolysosomes, has been studied extensively as a caspase-independent cell death pathway and has been associated with ischemia and reperfusion in the heart and brain [4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its antioxidant property, crocin may be used as a pharmacological agent in cases that results in cerebral ischemia (Lee et al 2005). The modern pharmacological studies have shown that saffron extract and active contents of it have anti-tumor effects, radical scavenger properties, hypolipemic effect and memory-improving effect (He et al 2005;Sugiura et al 1994;Zhang et al 1994).…”
Section: Discussionmentioning
confidence: 99%